The english as a foreign language / lingua franca debate: sensitising teachers of english as a foreign language towards teaching english as a lingua franca (2012)
The function of English as a lingua franca for communication needs rethinking in the teaching of English as a foreign language classroom as a consequence of globalisation. The present contribution is an empirical study carried out in an Italian university environment which aims to show how teachers should take on board awareness raising activities in the recognition of other varieties of English which, albeit not exploited as benchmarks for language testing and certification, must nevertheless boast a relevant place in the global scenario. This can be achieved in practical terms by interrogating an expressly made corpus of Chinese English news texts and carrying out simple concordance activities. Debido a los procesos de globalización, la función del inglés como herramienta internacional o como lengua franca para la comunicación exige un replanteamiento de la enseñanza del inglés como idioma extranjero. En este artículo se presenta un estudio empírico llevado a cabo en un contexto universitario italiano que pretende mostrar cómo los docentes deberían desempeñar actividades para facilitar el reconocimiento de otras variedades del inglés que, al no ser utilizadas como modelos de evaluación y certificación lingüística, exigen en cambio una mayor atención en el escenario global. En la práctica, esto puede realizarse analizando un corpus específico de textos periodísticos en inglés chino y llevando a cabo actividades sencillas de concordancias.